KADAR SERUM 25 (OH) D PADA IBU HAMIL TRIMESTER III YANG MENGGUNAKAN HIJAB DI WILAYAH KOTA MAKASSAR - Siswati Rahmadyana; Aminuddin Aminuddin; Mappaware Nasrudin A; P Prihantono; Sinrang A Wardihan; Nilawati Andi (Poltekkes Kemenkes Bandung, 2020)
ObjectiveThis study aimed to determine the serum levels of 25 (OH) D in the third trimester pregnant women who use the hijab in RSIA Sitti Khadijah I Makassar. Method: The study design was cross-sectional study to study as many as 62 respondents taken by purposive sampling technique in the third trimester pregnant women in RSIA Sitti Khadijah I Makassar using questionnaires, and measurement of serum levels of 25 (OH) D by using CLIA (Chemiluminescence Immunoassay) in PRODIA laboratory, in November-December 2019. this study tested using the mann-whitney statistical analysis. Results:Statistical test results showed that there was no difference in serum levels of vitamin D in pregnant women without the hijab and veil (p> 0.05), though the average and ranks serum levels of vitamin D in pregnant women was kept higher than pregnant women without hijab.